School failure in students of high school education of public schools of Peru, 2005-2010, and their associated factors - Latorre Ariño, Marino (2018)
The present investigation seeks to determine the scholastic failure in secondary education in Peru between the years 2005-2010 and to identify the factors associated with this failure. This investigation is Non-experimental, multifactorial explanatory with a retrospective cross-sectional ex post facto design. It proposes a theoretical explanatory model of school failure from the ecological-systemic paradigm. The sample is 55% of high school students in Peru. To determine the influence of the intervening variables, statistical-mathematical instruments were used, performing a descriptive statistical analysis, a factorial analysis and a regression model β was applied. The conclusion reached is that, although school failure is the consequence of multiple factors, the most influential variables are the sociocultural and socio-economic environment in which the student lives. The results obtained have allowed an epidemiological study of school failure in Peru using a mathematical model of boxes, designed expressly for this research, in order to make predictions about school failure in Peru in the next five years.